Air shower radio signal electric field orientation as measured with the Astroneu Cosmic Ray telescope. Issue 1 (1st November 2022) - Nonis, S; Leisos, A; Tsirigotis, A; Bourlis, G; Papageorgiou, K; Gkialas, I; Manthos, I; Tzamarias, S
Abstract: The Astroneu cosmic ray telescope is a small scale hybrid array consisting of both scintillator counters and electromagnetic radiation detectors in the radio-wave frequency (RF) band (antennas). Astroneu was installed and operated in the area of the Hellenic Open University (HOU) campus near the city of Patras in Greece. In the present development phase, the Astroneu telescope includes two stations consisting of 3 scintillation detectors modules (SDM) and one RF antenna while a third station includes 3 particle detectors and 4 RF antennas (3SDM-4RF). In this context we present the resent results from both the 3SDM-4RF autonomous station and simulations related to the estimation of the direction of the electric field emitted during the air shower development. The electric field measured in the ground level is the superposition of the two dominant emission mechanism, the time depended transverse current induced by the geomagnetic field and the net negative charge variation at the shower front. Since the electric field emitted by the two contributions is polarized in different directions the measured electric field in the ground encloses information about the charge-excess to geomagnetic ratio (CGR). Furthermore the orientation of the electric field emitted by charge-excess mechanism is strongly depends from the distance to the shower core (the intersection of the shower axis with the ground level). In this study we use the core information as reconstructed using the radio data and simulations. The estimated charge-excess to geomagnetic ratio is in agreement with previous studies which reveals that the shower core reconstruction method is efficient. Finally we report on that CGR measurements can be used for an efficient noise rejection in a future self trigger mode